2020
DOI: 10.1007/s00261-020-02641-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality Comparison of 3 Tesla multiparametric MRI of the prostate using a flexible surface receiver coil versus conventional surface coil plus endorectal coil setup

Abstract: Purpose To subjectively and quantitatively compare the quality of 3 Tesla magnetic resonance imaging of the prostate acquired with a novel flexible surface coil (FSC) and with a conventional endorectal coil (ERC). Methods Six radiologists independently reviewed 200 pairs of axial, high-resolution T2-weighted and diffusion-weighted image data sets, each containing one examination acquired with the FSC and one with the ERC, respectively. Readers selected their preferred examination from each pair and assessed ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The coils could not provide a comparable SNR efficiency compared with the two 48-channel coils used in the clinical whole-body MRI systems. Lightweight flexible RF receive coils with more channels 27,28 may be used to further improve the SNR for prostate MRI. We also note that the SNR calculation was based on the magnitude signal, and the ADC was calculated by a linear fitting.…”
Section: Discussionmentioning
confidence: 99%
“…The coils could not provide a comparable SNR efficiency compared with the two 48-channel coils used in the clinical whole-body MRI systems. Lightweight flexible RF receive coils with more channels 27,28 may be used to further improve the SNR for prostate MRI. We also note that the SNR calculation was based on the magnitude signal, and the ADC was calculated by a linear fitting.…”
Section: Discussionmentioning
confidence: 99%
“…At the same magnetic field strength, it is of no surprise that there are numerous studies that validate the proposed superiority in SNR that results from using an ERC 30–32 . Few studies have evaluated CNR, although Ullrich et al 31 did not observe improved discrimination between benign and cancerous prostate.…”
Section: Scanner Factorsmentioning
confidence: 95%
“…29 At the same magnetic field strength, it is of no surprise that there are numerous studies that validate the proposed superiority in SNR that results from using an ERC. [30][31][32] Few studies have evaluated CNR, although Ullrich et al 31 did not observe improved discrimination between benign and cancerous prostate. The expected improvement in image quality, as rated by radiologists on a 1 to 5 Likert scale, has been shown for DWI 32,33 and T2-WI 34 but certain studies have also reported no superiority with either set up.…”
Section: Erc Usementioning
confidence: 98%
See 2 more Smart Citations